A CRITICAL REVIEW ON VISHTINDUKADI VATI - kumar, Praveen; Porte, Sharad M; Meena, Sheetal (International Research Journal of Ayurveda & Yoga, 2024)
Vishtindukadi vati1is Ayurvedic drug mentioned in Ras tantra sara and sidha prayoga samgraha1. The main Content of vishtindukadi vati is the kuchla, along with maricha, chincha phala and phugphala, indicated in opium addiction. The main contents of vishatindukaadi vati are Kupilu1 which having properties like vata-shamak, chitta-avasadahar (antidepressant properties) and hridya daurbalyahar (cardiac tonic). Also Kupilu and Pugphal has pharmacological actions opposite to opium withdrawal symptoms Pharmacological preparation of Kupilu calm down the withdrawal effect of opium like anxiety and agitation by its Chitavsadhar property and Running nose, Diarrhea by it’s Grahi property. Muscular pain and Joint Pain by its vatshamak property. All these drugs are having mainly katu-tikta rasa, ruksha, ushna, tikshna gunaas, ushna virya and vata kaphagnadoshaghnata.